Copyright for the Digital Age - A Call for Legislative Reversibility - Felix Oberholzer-Gee (Swiss Journal of Economics and Statistics, 2011)
Policymakers tend to adopt too narrow a view of the creative industries when determining the desirability of copyright protection. In these industries, authors will often create new works despite weak protection. As recent developments in the music industry illustrate, markets for complements alone can be sufficiently lucrative to entice artists to remain active even when copyright is seriously weakened. However, the value of complements is difficult to forecast. As a result, lawmakers will often set inappropriate copyright terms. In this note, I call for an approach to copyright legislation that makes it feasible to correct these unavoidable mistakes.
Keywords: L51; O34; O38; 330; Copyright; Creative Industries; Regulation